How Does Silicon Mediate Plant Water Uptake and Loss Under Water Deficiency? - Chen, Daoqian; Wang, Shiwen; Yin, Lina; Deng, Xiping (Frontiers in Plant Science, 2018)
In plants, water deficiency can result from a deficit of water from the soil, an obstacle to the uptake of water or the excess water loss; in these cases, the similar consequence is the limitation of plant growth and crop yield. Silicon (Si) has been widely reported to alleviate the plant water status and water balance under variant stress conditions in both monocot and dicot plants, especially under drought and salt stresses. However, the underlying mechanism is unclear. In addition to the regulation of leaf transpiration, recently, Si application was found to be involved in the adjustment of root hydraulic conductance by up-regulating aquaporin gene expression and concentrating K in the xylem sap. Therefore, this review discusses the potential effects of Si on both leaf transpiration and root water absorption, especially focusing on how Si modulates the root hydraulic conductance. A growing number of studies support the conclusion that Si application improves plant water status by increasing root water uptake, rather than by decreasing their water loss under conditions of water deficiency. The enhancement of plant water uptake by Si is achievable through the activation of osmotic adjustment, improving aquaporin activity and increasing the root/shoot ratio. The underlying mechanisms of the Si on improving plant water uptake under water deficiency conditions are discussed.